System design and application for evaluation of blocking agility in volleyball - Ho, C.-S.; Lin, K.-C.; Chen, K.-C.; Chiu, P.-K.; Chen, H.-J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2016)
The agility T-test and countermovement jump test have long been used to examine the agility of athletes. However, for some sports, newer systems of evaluation are being designed for specific movements. The goal of this study was to design a blocking agility system and apply it to analyzing the efficiency of 6 weeks of plyometric training on volleyball players. A total of 26 male volleyball players in Taiwan participated in the study. The participants were divided into a plyometric training group and a control group. The agility T-test, countermovement jump test, and blocking agility test were used to examine the influence of plyometric training on the blocking agility of volleyball players. A single-factor analysis of covariance was applied to obtain the variables for the two groups. There was no significant difference between the groups on the agility T-test. On the countermovement jump test and blocking agility test, the plyometric training group performed significantly better than the control group. Also, the power values of blocking agility were higher than 90%, which demonstrated very good validity. The results of this study indicate that appropriate plyometric training can increase the rate of force development for vertical jumps and significantly enhance the combined agility of volleyball players in terms of lateral-movement speed and quickness, which enable players to rapidly perform blocking actions.